Predictive Value of Geriatric Nutritional Risk Index in Patients With Coronary Artery Disease: A Meta-Analysis - Fan, Yu; He, Lian; Zhou, Yongjing; Man, Changfeng (Frontiers in Nutrition, 2021)
Background: Low Geriatric Nutritional Risk Index (GNRI) has been identified as an index of impaired nutritional state. The objective of meta-analysis was to assess the association of GNRI with adverse outcomes in patients with coronary artery disease (CAD). Methods: Relevant studies were identified by comprehensively searching PubMed and Embase databases through May 2021. Studies assessing the association of GNRI with all-cause mortality or major adverse cardiovascular events (MACEs) in patients with CAD were included. The predictive value of GNRI was summarized by pooling multivariable adjusted risk ratios (RR) with 95% confidence intervals (CI) for per GNRI point decrease or the lowest vs. the highest GNRI group. Results: A total of 8 studies involving 9277 CAD patients were analyzed. Meta-analysis showed that the lowest GNRI was associated with higher risk of all-cause mortality (RR 2.10; 95% CI 1.68–2.63) and MACEs (RR 2.84; 95% CI 1.56–5.16), respectively. Furthermore, per point decrease in GNRI was associated with 8% and 10% additional risk of all-cause mortality and MACEs. Subgroup analysis indicated that the value of low GNRI in predicting all-cause mortality was not affected by subtype of patients or follow-up duration. Conclusion: Low GNRI score at baseline was associated with higher risk of all-cause mortality and cardiovascular events in CAD patients. Nutritional state estimated by GNRI score could provide important predictive information in patients with CAD.